IMPACT OF FRAILTY ON OUTCOMES IN SURGICAL PATIENTS: A SYSTEMATIC REVIEW AND META-ANALYSIS. (16th November 2018) - Panayi, A; Orkaby, A; Sakthivel, D; Endo, Y; Orgill, D; Neppl, R; Javedan, H; Sinha, I
Abstract: Background: The concept of frailty was introduced to explain the discrepancies that exist between patients' chronological and physiological age. The efficacy of the modified frailty index (mFI) to predict surgical risk is not clear. We sought to synthesize the current literature to quantify the impact of frailty as a prognostic indicator across all surgical specialties. Study Design: Pubmed and Cochrane were screened from inception to 1 January 2018 to select studies utilizing the mFI as a post-operative indicator of surgery. The random-effects model was used to calculate the Risk Ratios (RR). Primary outcomes: post-operative complications, re-admission, re-operation, discharge to a skilled care facility, and mortality. Results: This meta-analysis of 16 studies randomizes 683, 487 patients, 444, 885 frail, from gastrointestinal, vascular, orthopedic, urogenital, head and neck, emergency, neurological, oncological, cardiothoracic, as well as general surgery cohorts. Frail patients were more likely to experience complications (RR 1.48, 95%CI 1.35–1.61; p<0.001), major complications (RR 2.03, 95%CI 1.26–3.29; p=0.004), and wound complications (RR 1.52, 95%CI 1.47–1.57; p<0.001). Furthermore, frail patients had higher risk of readmission (RR 1.61, 95%CI 1.44–1.80; p<0.001) and discharge to skilled care (RR 2.15, 95%CI 1.92–2.40; p<0.001). The risk of mortality was 4.19 times more likely in frail patients (95% CI 2.96—5.92; p< 0.001). Conclusion: This study is the first to synthesize the evidence across multiple surgical specialties and demonstrates that the mFI is an underappreciated prognostic indicator that strongly correlates with the risk of post-surgical morbidity and mortality. This supports that formal incorporation of pre-operative frailty assessment improves surgical decision-making.